Mechanisms of a Sustained Anti‐inflammatory Drug Response in Alveolar Macrophages Unraveled with Mathematical Modeling. (13th December 2020) - Nyman, Elin; Lindh, Maria; Lövfors, William; Simonsson, Christian; Persson, Alexander; Eklund, Daniel; Bäckström, Erica; Fridén, Markus; Cedersund, Gunnar
Abstract : Both initiation and suppression of inflammation are hallmarks of the immune response. If not balanced, the inflammation may cause extensive tissue damage, which is associated with common diseases, e.g., asthma and atherosclerosis. Anti‐inflammatory drugs come with side effects that may be aggravated by high and fluctuating drug concentrations. To remedy this, an anti‐inflammatory drug should have an appropriate pharmacokinetic half‐life or better still, a sustained anti‐inflammatory drug response. However, we still lack a quantitative mechanistic understanding of such sustained effects. Here, we study the anti‐inflammatory response to a common glucocorticoid drug, dexamethasone. We find a sustained response 22 hours after drug removal. With hypothesis testing using mathematical modeling, we unravel the underlying mechanism—a slow release of dexamethasone from the receptor–drug complex. The developed model is in agreement with time‐resolved training and testing data and is used to simulate hypothetical treatment schemes. This work opens up for a more knowledge‐driven drug development to find sustained anti‐inflammatory responses and fewer side effects.